A solvent-resistant cyclodextrin nanofiltration membrane, a preparation method and application thereof
Patent Information
- Application Number
- CN202611441962.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-20
AI Technical Summary
但是,这类含环糊精的膜用于分离脂溶性目标物时,实际选择性不及预期,对目标物的识别能力有限,且在长期运行中存在通量和截留率下降的问题,膜的稳定性有待提高
[0035]1.本发明在界面聚合前以紫罗兰酮类化合物对单-6-乙二胺基-β-环糊精的空腔进行占位包合,界面聚合完成后再以乙醇洗脱紫罗兰酮类化合物。占位期间,紫罗兰酮类化合物占据环糊精空腔,参与界面聚合的均苯三甲酰氯和生长中的交联链段无法进入空腔内部,也难以封堵空腔开口,乙醇洗脱后留下的空腔保持开放且取向较为一致。开放的空腔与虾青素酯端部的环状结构尺寸相近,可对其产生包合作用,膜对虾青素酯的滞留同时来自空腔识别与分子量筛分,而不只是分子量筛分,红球藻乙醇提取液中与虾青素酯分子量相近的叶绿素、甘油三酯得以与虾青素酯区分开。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of haematococcus pluvialis separation and filtration membrane technology, specifically relating to a cyclodextrin solvent-resistant nanofiltration membrane, its preparation method, and its application. Background Technology
[0002] Haematococcus pluvialis is a freshwater single-celled green alga that can accumulate large amounts of astaxanthin under adverse conditions, making it a major raw material for the industrial production of natural astaxanthin. Astaxanthin belongs to the ketocarotenoid family and has strong antioxidant capabilities, widely used in food, health food, aquatic feed, and cosmetics. Astaxanthin in Haematococcus pluvialis rarely exists in free form; the vast majority is esterified with fatty acids to form astaxanthin esters, with monoesters accounting for approximately 70% and diesters for approximately 25%. The esterified fatty acids are mainly oleic acid, linoleic acid, and palmitic acid.
[0003] In industrial production, Haematococcus pluvialis is first subjected to cell wall disruption, and then extracted with solvents such as ethanol to obtain an ethanol extract containing astaxanthin esters. This extract has a complex composition, containing not only astaxanthin esters but also free fatty acids, chlorophyll, triglycerides, and a small amount of pigment degradation products. It needs to be concentrated and purified to obtain an oleoresin product with a high astaxanthin ester content.
[0004] Currently, vacuum distillation is commonly used to concentrate the ethanol extracts mentioned above. Astaxanthin esters are sensitive to heat, light, and oxygen. During distillation, the feed solution is heated for a prolonged period, which easily leads to oxidative degradation and cis-trans isomerization of astaxanthin esters, resulting in a decrease in retention. At the same time, small molecule impurities such as free fatty acids in the extract are enriched during concentration, increasing the acid value of the concentrate and increasing the burden on subsequent purification. The purification process generally uses macroporous resin column chromatography. Column chromatography is a batch operation with long loading, elution, and regeneration cycles, large consumption of solvents such as ethanol, and small batch processing capacity, making continuous production difficult. Furthermore, a significant amount of astaxanthin ester is lost during repeated adsorption, elution, and transfer within the column.
[0005] Membrane separation technology operates at room temperature, involves no phase change, and can be continuously operated, making it one of the development directions to replace distillation and concentration. Solvent-resistant nanofiltration membranes can operate for extended periods in organic solvents and have been used for the concentration and solvent recovery of natural product extracts. However, existing solvent-resistant nanofiltration membranes rely on molecular weight differences for sieving. In the ethanol extract of *Haemophilus polyphylla*, astaxanthin monoesters have a molecular weight of approximately 870 Da, astaxanthin diesters approximately 950-1150 Da, chlorophyll a approximately 907 Da, and triglycerides approximately 850-900 Da. These molecular weights overlap, making it impossible to separate astaxanthin esters from chlorophyll and triglycerides using molecular weight sieving alone. Free fatty acids have a molecular weight of approximately 280 Da. Although they can pass through nanofiltration membranes, ordinary solvent-resistant nanofiltration membranes lack selective retention capacity for astaxanthin esters, resulting in limited retention rates, low concentration factors, and difficulty in simultaneously achieving concentration and impurity removal.
[0006] Cyclodextrins, with their truncated conical cavity structure, can form inclusion complexes with size-matched hydrophobic groups. They have been incorporated into the selective layers of nanofiltration membranes for water treatment applications such as desalination, dye removal, and ion separation. There are also reports of introducing cyclodextrin-containing metal-organic frameworks into membranes to improve membrane performance. However, when used to separate lipid-soluble analytes, these cyclodextrin-containing membranes exhibit lower-than-expected selectivity, limited recognition ability, and a decline in flux and rejection rate during long-term operation, indicating a need to improve membrane stability. A search revealed no reports of using cyclodextrin-containing nanofiltration membranes for the concentration and purification of astaxanthin esters from Haematococcus pluvialis ethanol extract.
[0007] In summary, developing a solvent-resistant nanofiltration membrane capable of selectively retaining astaxanthin esters and simultaneously removing free fatty acids in an ethanol system, while maintaining stable operation, to achieve concentration and purification of Haematococcus pluvialis ethanol extract at room temperature and avoid heat loss of astaxanthin esters, is a technical problem that needs to be solved by those skilled in the art. Therefore, it is necessary to design a cyclodextrin solvent-resistant nanofiltration membrane, its preparation method, and its applications. Summary of the Invention
[0008] To overcome the shortcomings of existing technologies, a cyclodextrin solvent-resistant nanofiltration membrane is provided, along with its preparation method and applications.
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] A cyclodextrin-resistant solvent-resistant nanofiltration membrane, the nanofiltration membrane comprising a cross-linked polyimide hollow fiber support layer and a selective layer attached to the outer surface of the cross-linked polyimide hollow fiber support layer; the selective layer comprising a polyamide-polyester cross-linked network and cyclodextrin metal-organic framework nanosheets embedded in the polyamide-polyester cross-linked network, wherein the polyamide-polyester cross-linked network is formed by interfacial polymerization of mono-6-ethylenediamino-β-cyclodextrin, piperazine, and trimesoyl chloride.
[0011] The thickness of the selective layer is 80-200 nm, the thickness of the cyclodextrin metal-organic framework nanosheet is 50-200 nm, and the thickness of the cyclodextrin metal-organic framework nanosheet is less than the thickness of the selective layer.
[0012] The cross-linked polyimide hollow fiber support layer has a molecular weight cutoff of 10,000-20,000 Da. The cross-linked polyimide hollow fiber support layer is obtained by dry-jet wet spinning of polyimide spinning solution to obtain polyimide hollow fibers, followed by composite cross-linking.
[0013] The polyimide spinning solution uses N-methylpyrrolidone as a solvent, and the mass fraction of polyimide is 18-22%. The polyimide spinning solution also includes polyvinylpyrrolidone, and the mass ratio of polyvinylpyrrolidone to polyimide in the polyimide spinning solution is 1:(2-5).
[0014] The composite crosslinking process involves immersing polyimide hollow fibers in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane, crosslinking at room temperature for 12-24 h, and then immersing them in a mixture of water and ethanol at a volume ratio of 1:1, and keeping them at 40-50°C for 2-4 h.
[0015] In the isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane, the volume fraction of ethylenediamine is 5-10%, and the mass ratio of 3-aminopropyltriethoxysilane to ethylenediamine is 1:(5-20).
[0016] The preparation of the cyclodextrin metal-organic framework nanosheets includes the following steps:
[0017] (1) Crystallization: Dissolve γ-cyclodextrin and potassium hydroxide in pure water at a molar ratio of 1:8, with a concentration of γ-cyclodextrin of 20-40 g / L. Add anhydrous ethanol and mix. The volume ratio of pure water to anhydrous ethanol is 1:(1-2). Crystallize for 2-6 h at an ultrasonic power of 200-400 W, a frequency of 40 kHz, and a temperature of 25-35℃. Centrifuge at 8000-10000 r / min for 5-10 min, collect the precipitate, wash 2-3 times with anhydrous ethanol, and vacuum dry at 40-50℃ to obtain cyclodextrin metal-organic framework crystals.
[0018] (2) Exfoliation and classification: The cyclodextrin metal-organic framework crystals are dispersed in anhydrous ethanol at a concentration of 10-20 g / L and exfoliated for 1-3 h under ultrasonic power of 300-500 W, with the temperature of the circulating water controlled not to exceed 35℃, to obtain the exfoliated dispersion; the exfoliated dispersion is classified by differential centrifugation, first centrifuging at 1500-2000 r / min for 10-15 min, discarding the precipitate and taking the supernatant, then centrifuging at 4000-6000 r / min for 15-20 min, discarding the precipitate and taking the supernatant, and finally centrifuging at 8000-10000 r / min for 20-30 min, discarding the supernatant and taking the precipitate, wherein the precipitate is a nanosheet with a thickness of 50-200 nm;
[0019] (3) Grafting amine groups: The nanosheets are dispersed in anhydrous ethanol at a concentration of 5-10 g / L, and 3-aminopropyltriethoxysilane is added. The mass ratio of 3-aminopropyltriethoxysilane to the nanosheets is 1:(10-20). The mixture is stirred at 40-60℃ for 4-8 h, collected by centrifugation at 8000-10000 r / min for 8-10 min, washed 2-3 times with anhydrous ethanol, and dried under vacuum at 40-50℃ to obtain cyclodextrin metal-organic framework nanosheets with amine groups grafted on the surface.
[0020] A method for preparing a cyclodextrin solvent-resistant nanofiltration membrane, the method comprising the following steps:
[0021] (i) Inclusion: Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent and heated to 50-60℃ to dissolve. An ethanol solution of ionone compounds was added dropwise. The molar ratio of mono-6-ethylenediamino-β-cyclodextrin to ionone compounds was 1:(1-1.2). The mixture was stirred at 40-50℃ for 4-12 h to include the compounds. The inclusion solution was concentrated under reduced pressure until the ethanol volume fraction was less than 5%. After centrifugation, the precipitated free ionone compounds were discarded. The solution was diluted with pure water to obtain the inclusion monomer solution.
[0022] (ii) Preparation of aqueous phase: piperazine is added to the inclusion monomer solution, the molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine is 1:(0.2-1), the total concentration of mono-6-ethylenediamino-β-cyclodextrin and piperazine is 10-30 g / L, sodium carbonate is added to adjust the pH to 10-11, and the aqueous phase is obtained;
[0023] (iii) Preparation of the oil phase: Dissolve pyromellitic chloride in n-hexane to obtain the oil phase;
[0024] (iv) Aqueous phase immersion: Immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 1-3 min, then remove and drain;
[0025] (v) Pre-coating: The hexane and isopropanol mixed dispersion of cyclodextrin metal-organic framework nanosheets is coated on the outer surface of the support film and left to dry.
[0026] (vi) Interface polymerization: Within 5 minutes after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain positive pressure, and the outer surface reacts with the oil phase for 1-5 minutes. After removal, heat treatment is performed.
[0027] (vii) Ethanol elution: The membrane obtained in step (vi) is eluted with ethanol to obtain a cyclodextrin solvent-resistant nanofiltration membrane.
[0028] In step (I), the preparation method of the mono-6-ethylenediamine-β-cyclodextrin is as follows: β-cyclodextrin is dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride is added dropwise at 0-5℃. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride is 1:(1-1.2). The pH is maintained at 10-11 with sodium hydroxide solution, and the reaction is carried out for 2-4 h. The mixture is then recrystallized from cold water to obtain mono-6-p-toluenesulfonyl-β-cyclodextrin. Mono-6-p-toluenesulfonyl-β-cyclodextrin is then mixed with ethylenediamine at a molar ratio of 1:(20-50), and the mixture is reacted at 60-80℃ for 6-12 h. The mixture is then precipitated with acetone and dried.
[0029] In step (i), the volume ratio of water to ethanol in the mixed solvent is (3-5):1. After the inclusion in step (i) is completed, the inclusion rate is determined by ultraviolet spectrophotometry, and the inclusion rate is not less than 80%.
[0030] In step (v), the concentration of cyclodextrin metal-organic framework nanosheets in the dispersion is 0.5-2 g / L, the solvent is a mixed solvent of n-hexane and isopropanol in a volume ratio of (4-10):1, and the coating is applied 2-4 times.
[0031] In step (vi), the nitrogen positive pressure is 0.01-0.05 MPa, the concentration of trimesoyl chloride in the oil phase is 0.5-2 g / L, the heat treatment is 60-80℃ for 5-10 min, and after the heat treatment, the membrane is contacted with a hexane solution with a trimesoyl chloride concentration of 0.1-0.3 g / L for 30-60 s and dried at 40-60℃.
[0032] In step (vii), the elution endpoint is determined by gas chromatography, where the content of ionone compounds is below the detection limit. The ethanol eluent is then distilled under reduced pressure, and the distilled ethanol is reused in step (vii). The ionone compounds at the bottom of the vessel are reused in step (i).
[0033] An application of a cyclodextrin-resistant solvent-resistant nanofiltration membrane, wherein the cyclodextrin-resistant solvent-resistant nanofiltration membrane is used for the concentration and purification of astaxanthin esters in the ethanol extract of Haematococcus pluvialis.
[0034] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0035] 1. In this invention, ionone compounds are used to occupy and encapsulate the cavity of mono-6-ethylenediamino-β-cyclodextrin before interfacial polymerization. After interfacial polymerization, the ionone compounds are eluted with ethanol. During the encapsulation period, the ionone compounds occupy the cyclodextrin cavity, preventing the trimesoyl chloride and growing crosslinked segments participating in interfacial polymerization from entering the cavity and blocking the cavity opening. The cavity remaining after ethanol elution remains open and has a relatively consistent orientation. The open cavity is similar in size to the ring structure at the end of astaxanthin ester, which can encapsulate it. The membrane retention of astaxanthin ester comes from both cavity recognition and molecular weight sieving, not just molecular weight sieving. Chlorophyll and triglycerides with similar molecular weights to astaxanthin ester in the ethanol extract of *Hydrocotyle vulgaris* can be distinguished from astaxanthin ester.
[0036] 2. The selective layer of this invention embeds cyclodextrin metal-organic framework nanosheets. The nanosheets have a regular cavity arrangement and a large free volume, providing additional transport channels for ethanol and improving membrane flux without reducing retention capacity. The nanosheets are pre-coated and attached to the outer surface of the support layer before contacting the oil phase. They do not participate in the preparation of the oil phase. The amine groups grafted on their surface do not react prematurely with trimesoyl chloride during oil phase preparation, but instead integrate into the polyamide-polyester crosslinking network at the moment of interfacial polymerization. A chemical bond is formed between the nanosheets and the crosslinking network, making them less prone to loss from the selective layer during long-term operation.
[0037] 3. This invention employs a cross-linked polyimide hollow fiber support layer. Ethylenediamine performs ring-opening cross-linking on the polyimide, preventing the membrane from swelling and deforming easily after prolonged immersion in ethanol. The amine group at one end of 3-aminopropyltriethoxysilane undergoes a ring-opening reaction with the imide ring of the polyimide, covalently linking siloxane groups to the polyimide chain. The siloxane groups at the other end undergo hydrolysis and condensation to form a siloxane cross-linked structure on the fiber surface. Residual amine and silanol groups on the surface participate in the selective layer formation reaction during interfacial polymerization. The selective layer is anchored to the outer surface of the support layer and is not easily peeled off under prolonged ethanol rinsing. Secondary contact after heat treatment seals the pinholes in the selective layer and the exposed edges of the nanosheets, ensuring stable membrane retention across batches.
[0038] 4. The cyclodextrin-resistant nanofiltration membrane of the present invention is used for the concentration and purification of astaxanthin esters in the ethanol extract of Haematococcus pluvialis. The concentration is carried out at room temperature, and the astaxanthin esters do not undergo a heating process, thus reducing the losses caused by oxidative degradation and cis-trans isomerization. The free fatty acids have a small molecular weight and no cyclic end structure, so their interaction with the cavity is weak, and they are removed with the ethanol permeate. Impurities are removed during concentration, and the acid value of the resulting astaxanthin ester concentrate decreases accordingly. The ethanol eluent is recovered by vacuum distillation, and both ethanol and ionone compounds can be reused, reducing solvent consumption. The concentration process can be run continuously. Attached Figure Description
[0039] Figure 1This is a process flow diagram of a method for preparing a cyclodextrin solvent-resistant nanofiltration membrane. Detailed Implementation
[0040] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0041] The technical solution of this invention is as follows:
[0042] A cyclodextrin-resistant solvent-resistant nanofiltration membrane, the nanofiltration membrane comprising a cross-linked polyimide hollow fiber support layer and a selective layer attached to the outer surface of the cross-linked polyimide hollow fiber support layer; the selective layer comprising a polyamide-polyester cross-linked network and cyclodextrin metal-organic framework nanosheets embedded in the polyamide-polyester cross-linked network, wherein the polyamide-polyester cross-linked network is formed by interfacial polymerization of mono-6-ethylenediamino-β-cyclodextrin, piperazine, and trimesoyl chloride.
[0043] The thickness of the selective layer is 80-200 nm, the thickness of the cyclodextrin metal-organic framework nanosheet is 50-200 nm, and the thickness of the cyclodextrin metal-organic framework nanosheet is less than the thickness of the selective layer.
[0044] The cross-linked polyimide hollow fiber support layer has a molecular weight cutoff of 10,000-20,000 Da. The cross-linked polyimide hollow fiber support layer is obtained by dry-jet wet spinning of polyimide spinning solution to obtain polyimide hollow fibers, followed by composite cross-linking.
[0045] The polyimide spinning solution uses N-methylpyrrolidone as a solvent, and the mass fraction of polyimide is 18-22%. The polyimide spinning solution also includes polyvinylpyrrolidone, and the mass ratio of polyvinylpyrrolidone to polyimide in the polyimide spinning solution is 1:(2-5).
[0046] The composite crosslinking process involves immersing polyimide hollow fibers in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane, crosslinking at room temperature for 12-24 h, and then immersing them in a mixture of water and ethanol at a volume ratio of 1:1, and keeping them at 40-50°C for 2-4 h.
[0047] In the isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane, the volume fraction of ethylenediamine is 5-10%, and the mass ratio of 3-aminopropyltriethoxysilane to ethylenediamine is 1:(5-20).
[0048] The preparation of the cyclodextrin metal-organic framework nanosheets includes the following steps:
[0049] (1) Crystallization: Dissolve γ-cyclodextrin and potassium hydroxide in pure water at a molar ratio of 1:8, with a concentration of γ-cyclodextrin of 20-40 g / L. Add anhydrous ethanol and mix. The volume ratio of pure water to anhydrous ethanol is 1:(1-2). Crystallize for 2-6 h at an ultrasonic power of 200-400 W, a frequency of 40 kHz, and a temperature of 25-35℃. Centrifuge at 8000-10000 r / min for 5-10 min, collect the precipitate, wash 2-3 times with anhydrous ethanol, and vacuum dry at 40-50℃ to obtain cyclodextrin metal-organic framework crystals.
[0050] (2) Exfoliation and classification: The cyclodextrin metal-organic framework crystals are dispersed in anhydrous ethanol at a concentration of 10-20 g / L and exfoliated for 1-3 h under ultrasonic power of 300-500 W, with the temperature of the circulating water controlled not to exceed 35℃, to obtain the exfoliated dispersion; the exfoliated dispersion is classified by differential centrifugation, first centrifuging at 1500-2000 r / min for 10-15 min, discarding the precipitate and taking the supernatant, then centrifuging at 4000-6000 r / min for 15-20 min, discarding the precipitate and taking the supernatant, and finally centrifuging at 8000-10000 r / min for 20-30 min, discarding the supernatant and taking the precipitate, wherein the precipitate is a nanosheet with a thickness of 50-200 nm;
[0051] (3) Grafting amine groups: The nanosheets are dispersed in anhydrous ethanol at a concentration of 5-10 g / L, and 3-aminopropyltriethoxysilane is added. The mass ratio of 3-aminopropyltriethoxysilane to the nanosheets is 1:(10-20). The mixture is stirred at 40-60℃ for 4-8 h, collected by centrifugation at 8000-10000 r / min for 8-10 min, washed 2-3 times with anhydrous ethanol, and dried under vacuum at 40-50℃ to obtain cyclodextrin metal-organic framework nanosheets with amine groups grafted on the surface.
[0052] A method for preparing a cyclodextrin solvent-resistant nanofiltration membrane, such as... Figure 1 As shown, the preparation method includes the following steps:
[0053] (i) Inclusion: Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent and heated to 50-60℃ to dissolve. An ethanol solution of ionone compounds was added dropwise. The molar ratio of mono-6-ethylenediamino-β-cyclodextrin to ionone compounds was 1:(1-1.2). The mixture was stirred at 40-50℃ for 4-12 h to include the compounds. The inclusion solution was concentrated under reduced pressure until the ethanol volume fraction was less than 5%. After centrifugation, the precipitated free ionone compounds were discarded. The solution was diluted with pure water to obtain the inclusion monomer solution.
[0054] (ii) Preparation of aqueous phase: piperazine is added to the inclusion monomer solution, the molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine is 1:(0.2-1), the total concentration of mono-6-ethylenediamino-β-cyclodextrin and piperazine is 10-30 g / L, sodium carbonate is added to adjust the pH to 10-11, and the aqueous phase is obtained;
[0055] (iii) Preparation of the oil phase: Dissolve pyromellitic chloride in n-hexane to obtain the oil phase;
[0056] (iv) Aqueous phase immersion: Immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 1-3 min, then remove and drain;
[0057] (v) Pre-coating: The hexane and isopropanol mixed dispersion of cyclodextrin metal-organic framework nanosheets is coated on the outer surface of the support film and left to dry.
[0058] (vi) Interface polymerization: Within 5 minutes after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain positive pressure, and the outer surface reacts with the oil phase for 1-5 minutes. After removal, heat treatment is performed.
[0059] (vii) Ethanol elution: The membrane obtained in step (vi) is eluted with ethanol to obtain a cyclodextrin solvent-resistant nanofiltration membrane.
[0060] In step (I), the preparation method of the mono-6-ethylenediamine-β-cyclodextrin is as follows: β-cyclodextrin is dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride is added dropwise at 0-5℃. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride is 1:(1-1.2). The pH is maintained at 10-11 with sodium hydroxide solution, and the reaction is carried out for 2-4 h. The mixture is then recrystallized from cold water to obtain mono-6-p-toluenesulfonyl-β-cyclodextrin. Mono-6-p-toluenesulfonyl-β-cyclodextrin is then mixed with ethylenediamine at a molar ratio of 1:(20-50), and the mixture is reacted at 60-80℃ for 6-12 h. The mixture is then precipitated with acetone and dried.
[0061] In step (i), the volume ratio of water to ethanol in the mixed solvent is (3-5):1. After the inclusion in step (i) is completed, the inclusion rate is determined by ultraviolet spectrophotometry, and the inclusion rate is not less than 80%.
[0062] In step (v), the concentration of cyclodextrin metal-organic framework nanosheets in the dispersion is 0.5-2 g / L, the solvent is a mixed solvent of n-hexane and isopropanol in a volume ratio of (4-10):1, and the coating is applied 2-4 times.
[0063] In step (vi), the nitrogen positive pressure is 0.01-0.05 MPa, the concentration of trimesoyl chloride in the oil phase is 0.5-2 g / L, the heat treatment is 60-80℃ for 5-10 min, and after the heat treatment, the membrane is contacted with a hexane solution with a trimesoyl chloride concentration of 0.1-0.3 g / L for 30-60 s and dried at 40-60℃.
[0064] In step (vii), the elution endpoint is determined by gas chromatography, where the content of ionone compounds is below the detection limit. The ethanol eluent is then distilled under reduced pressure, and the distilled ethanol is reused in step (vii). The ionone compounds at the bottom of the vessel are reused in step (i).
[0065] An application of a cyclodextrin-resistant solvent-resistant nanofiltration membrane, wherein the cyclodextrin-resistant solvent-resistant nanofiltration membrane is used for the concentration and purification of astaxanthin esters in the ethanol extract of Haematococcus pluvialis.
[0066] It should be noted that during the inclusion process, ionone compounds enter the cavity of mono-6-ethylenediamino-β-cyclodextrin. The amine groups participating in interfacial polymerization are located on one side of the narrow edge of the cavity and extend outward through the ethylenediamine arm. The inclusion process does not affect the reactivity of the amine groups with trimesoyl chloride. In the dispersion used for pre-coating, isopropanol is miscible with both the aqueous phase and n-hexane. During coating, isopropanol acts as a bridging and wetting agent between the residual aqueous phase and the dispersion on the film surface, allowing the nanosheets to adhere uniformly to the outer surface of the supporting film. During the composite crosslinking, the amine group at one end of 3-aminopropyltriethoxysilane first undergoes a ring-opening reaction with the imide ring of the polyimide, covalently linking the siloxane group to the polyimide chain. The siloxane group at the other end hydrolyzes to silanols when kept at a temperature in a water and ethanol mixture, and they condense with each other to form a siloxane crosslinked structure. When the membrane is used for separation, astaxanthin esters enter the cavity with their terminal cyclic groups to form inclusions, while the main molecules remain outside the cavity. The cavity's recognition of the terminal cyclic groups and the sieving of the cross-linked network together achieve the retention of astaxanthin esters.
[0067] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products, wherein the polyimide is commercially available P84 type polyimide.
[0068] Example 1
[0069] Crosslinked polyimide hollow fiber support membrane was prepared. Polyimide was dissolved in N-methylpyrrolidone (22% by mass), and polyvinylpyrrolidone (1:3.5 by mass) was added. The mixture was stirred at 60°C to dissolve, allowed to stand to remove bubbles, and a polyimide spinning solution was obtained. Dry-jet wet spinning was performed with water as the core solution and water as the coagulation bath, with an air gap of 10 cm. The resulting hollow fibers were soaked in pure water for 36 h, then immersed in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane (5% by volume), with a 3-aminopropyltriethoxysilane to ethylenediamine mass ratio of 1:20. Crosslinking was carried out at room temperature for 18 h, followed by immersion in a 1:1 mixture of water and ethanol, and incubated at 40°C for 4 h. After removal, the membrane was washed three times with ethanol and dried at 45°C to obtain the crosslinked polyimide hollow fiber support membrane, with a molecular weight cutoff of 15000 Da.
[0070] Cyclodextrin metal-organic framework nanosheets were prepared. γ-Cyclodextrin and potassium hydroxide were dissolved in pure water at a molar ratio of 1:8, resulting in a γ-cyclodextrin concentration of 30 g / L. Anhydrous ethanol was added and mixed, with a water-to-ethanol volume ratio of 1:1. The mixture was crystallized at 400 W, 40 kHz, and 30 °C for 2 h. After centrifugation at 9000 r / min for 8 min, the precipitate was collected, washed three times with anhydrous ethanol, and dried under vacuum at 45 °C to obtain cyclodextrin metal-organic framework crystals. The crystals were dispersed in anhydrous ethanol at a concentration of 20 g / L and exfoliated at 400 W for 1 h, with the circulating water temperature controlled to not exceed 35 °C. The resulting exfoliated dispersion was first centrifuged at 1800 r / min for 12 min, discarding the precipitate and collecting the supernatant. Then, it was centrifuged at 5000 r / min for 18 min, discarding the precipitate and collecting the supernatant. Finally, it was centrifuged at 9000 r / min for 25 min, discarding the supernatant and collecting the precipitate. The nanosheet thickness was verified by atomic force microscopy, and the nanosheet thickness was 100 μm. nm; The nanosheets were dispersed in anhydrous ethanol at a concentration of 10 g / L, and 3-aminopropyltriethoxysilane was added. The mass ratio of 3-aminopropyltriethoxysilane to nanosheets was 1:15. The mixture was stirred at 40 °C for 8 h, collected by centrifugation at 9000 r / min for 9 min, washed three times with anhydrous ethanol, and dried under vacuum at 45 °C to obtain cyclodextrin metal-organic framework nanosheets with amine-grafted surfaces.
[0071] Preparation of mono-6-ethylenediamino-β-cyclodextrin: β-cyclodextrin was dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride was added dropwise at 2°C. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride was 1:1.1. The pH was maintained at 10.5 with sodium hydroxide solution, and the reaction was carried out for 2 h. After recrystallization from cold water, mono-6-p-toluenesulfonyl-β-cyclodextrin was obtained. This mono-6-ethylenediamino-β-cyclodextrin was then mixed with ethylenediamine at a molar ratio of 1:50 and reacted at 70°C for 6 h. After precipitation with acetone and drying, mono-6-ethylenediamino-β-cyclodextrin was obtained.
[0072] Preparation of cyclodextrin-resistant nanofiltration membranes. Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent of water and ethanol at a volume ratio of 5:1. The solution was heated to 55°C to dissolve, and an ethanol solution of β-ionone was added dropwise. The molar ratio of mono-6-ethylenediamino-β-cyclodextrin to β-ionone was 1:1. The mixture was stirred at 50°C for 8 h to encapsulate the monomers. The encapsulation rate was determined to be 86% by UV spectrophotometry. The encapsulation solution was concentrated under reduced pressure until the ethanol volume fraction was below 5%. After centrifugation, the precipitated free β-ionone was discarded, and the solution was diluted with pure water to obtain a site-occupied monomer solution. Piperazine was added to the solution, with a molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine of 1:0.2. The total concentration of mono-6-ethylenediamino-β-cyclodextrin and piperazine was 30 g / L. Sodium carbonate was added to adjust the pH to 10.5 to obtain an aqueous phase. Trimethylbenzene chloride was dissolved in n-hexane at a concentration of 0.5%. g / L, to obtain the oil phase; immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 3 min, remove and drain; disperse cyclodextrin metal-organic framework nanosheets grafted with amine groups in a mixed solvent of n-hexane and isopropanol at a volume ratio of 4:1, with a nanosheet concentration of 1.25 g / L; immerse the support membrane in the dispersion and remove, repeat the dip-coating 4 times, without drying; within 5 min after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain a positive pressure of 0.03 MPa, and the outer surface reacts with the oil phase for 1 min; after removal, heat-treat at 80℃ for 7.5 min, and then contact the membrane with a hexane solution with a concentration of 0.1 g / L for 60 min. The membrane was dried at 50°C. It was then eluted with ethanol in a circulating manner until the content of β-ionone in the eluent was lower than the detection limit by gas chromatography. The ethanol eluent was then distilled under reduced pressure, and the distilled ethanol was reused for elution. The β-ionone at the bottom of the vessel was reused for inclusion at the site to obtain a cyclodextrin solvent-resistant nanofiltration membrane. The selective layer was located on the outer surface of the hollow fiber, and the thickness of the selective layer was measured to be 180 nm.
[0073] Example 2
[0074] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0075] Crosslinked polyimide hollow fiber support membrane was prepared. Polyimide was dissolved in N-methylpyrrolidone (18% by mass), and polyvinylpyrrolidone (1:5 by mass) was added. The mixture was stirred at 60°C to dissolve, allowed to stand to remove bubbles, and a polyimide spinning solution was obtained. Dry-jet wet spinning was performed with water as the core solution and water as the coagulation bath, with an air gap of 10 cm. The resulting hollow fibers were soaked in pure water for 36 h, then immersed in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane (7.5% by volume, 1:5 by mass). Crosslinking was carried out at room temperature for 24 h, followed by immersion in a 1:1 mixture of water and ethanol at 45°C for 2 h. After removal, the membrane was washed three times with ethanol and dried at 45°C to obtain the crosslinked polyimide hollow fiber support membrane, with a molecular weight cutoff of 15000 Da.
[0076] Preparation of cyclodextrin metal-organic framework nanosheets. γ-Cyclodextrin and potassium hydroxide were dissolved in pure water at a molar ratio of 1:8, resulting in a γ-cyclodextrin concentration of 40 g / L. Anhydrous ethanol was added and mixed, with a water-to-ethanol volume ratio of 1:1.5. Crystallization was performed at 200 W ultrasonic power, 40 kHz frequency, and 35℃ for 4 h. The mixture was then centrifuged at 9000 r / min for 8 min, and the precipitate was collected. The precipitate was washed three times with anhydrous ethanol and dried under vacuum at 45℃ to obtain cyclodextrin metal-organic framework crystals. The crystals were dispersed in anhydrous ethanol at a concentration of 10 g / L and exfoliated at 500 W ultrasonic power for 2 h, with the circulating water temperature controlled to not exceed 35℃. The resulting exfoliated dispersion was centrifuged at 1800 r / min for 12 min, discarding the precipitate and collecting the supernatant. It was then centrifuged at 5000 r / min for 18 min, discarding the precipitate and collecting the supernatant. Finally, it was centrifuged at 9000 r / min for 25 min, discarding the supernatant and collecting the precipitate. The nanosheet thickness was verified by atomic force microscopy, and the nanosheet thickness was 100 μm. nm; The nanosheets were dispersed in anhydrous ethanol at a concentration of 5 g / L, and 3-aminopropyltriethoxysilane was added. The mass ratio of 3-aminopropyltriethoxysilane to nanosheets was 1:20. The mixture was stirred at 50 °C for 4 h, collected by centrifugation at 9000 r / min for 9 min, washed three times with anhydrous ethanol, and dried under vacuum at 45 °C to obtain cyclodextrin metal-organic framework nanosheets with amine-grafted surfaces.
[0077] Preparation of mono-6-ethylenediamino-β-cyclodextrin: β-cyclodextrin was dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride was added dropwise at 2°C. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride was 1:1.2. The pH was maintained at 10.5 with sodium hydroxide solution, and the reaction was carried out for 3 h. The mixture was then recrystallized from cold water to obtain mono-6-p-toluenesulfonyl-β-cyclodextrin. This mono-6-ethylenediamino-β-cyclodextrin was then mixed with ethylenediamine at a molar ratio of 1:20 and reacted at 80°C for 9 h. The mixture was precipitated with acetone and dried to obtain mono-6-ethylenediamino-β-cyclodextrin.
[0078] Preparation of cyclodextrin-resistant nanofiltration membranes. Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent of water and ethanol at a volume ratio of 3:1. The solution was heated to 60°C to dissolve, and an ethanol solution of β-ionone was added dropwise. The molar ratio of mono-6-ethylenediamino-β-cyclodextrin to β-ionone was 1:1.1. The mixture was stirred at 40°C for 12 h for inclusion, and the inclusion rate was determined to be 84% by UV spectrophotometry. The inclusion solution was concentrated under reduced pressure until the ethanol volume fraction was less than 5%. After centrifugation, the precipitated free β-ionone was discarded, and the solution was diluted with pure water to obtain a site-occupied inclusion monomer solution. Piperazine was added to the solution, with a molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine of 1:0.6. The total concentration of mono-6-ethylenediamino-β-cyclodextrin and piperazine was 10 g / L. Sodium carbonate was added to adjust the pH to 11 to obtain an aqueous phase. Trimethylbenzene chloride was dissolved in n-hexane at a concentration of 1.25 g / L. g / L, to obtain the oil phase; immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 1 min, remove and drain; disperse cyclodextrin metal-organic framework nanosheets grafted with amine groups in a mixed solvent of n-hexane and isopropanol at a volume ratio of 7:1, with a nanosheet concentration of 2 g / L; immerse the support membrane in the dispersion and remove, repeat the dip-coating twice, without drying; within 5 min after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain a positive pressure of 0.05 MPa, and the outer surface reacts with the oil phase for 3 min; remove and heat-treat at 60℃ for 10 min, then contact the membrane with a hexane solution with a concentration of 0.2 g / L for 30 minutes. The membrane was dried at 60℃ and eluted with ethanol until the content of β-ionone in the eluent was below the detection limit as detected by gas chromatography. The ethanol eluent was then distilled under reduced pressure, and the distilled ethanol was reused for elution. The β-ionone at the bottom of the vessel was reused for inclusion at the site to obtain a cyclodextrin solvent-resistant nanofiltration membrane. The selective layer was located on the outer surface of the hollow fiber, and the thickness of the selective layer was measured to be 130 nm.
[0079] Example 3
[0080] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0081] Crosslinked polyimide hollow fiber support membrane was prepared. Polyimide was dissolved in N-methylpyrrolidone (20% by mass), and polyvinylpyrrolidone (1:2 by mass) was added. The mixture was stirred at 60°C to dissolve, allowed to stand to remove bubbles, and a polyimide spinning solution was obtained. Dry-jet wet spinning was performed with water as the core solution and water as the coagulation bath, with an air gap of 10 cm. The resulting hollow fibers were soaked in pure water for 36 h, then immersed in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane (10% by volume) at 1:12.5 by mass of 3-aminopropyltriethoxysilane. Crosslinking was carried out at room temperature for 12 h, followed by immersion in a 1:1 mixture of water and ethanol at 50°C for 3 h. After removal, the membrane was washed three times with ethanol and dried at 45°C to obtain the crosslinked polyimide hollow fiber support membrane, with a molecular weight cutoff of 15000 Da.
[0082] Cyclodextrin metal-organic framework nanosheets were prepared. γ-Cyclodextrin and potassium hydroxide were dissolved in pure water at a molar ratio of 1:8, resulting in a γ-cyclodextrin concentration of 20 g / L. Anhydrous ethanol was added and mixed, with a water-to-ethanol volume ratio of 1:2. The mixture was crystallized at 300 W, 40 kHz, and 25 °C for 6 h. After centrifugation at 9000 r / min for 8 min, the precipitate was collected, washed three times with anhydrous ethanol, and vacuum dried at 45 °C to obtain cyclodextrin metal-organic framework crystals. The crystals were dispersed in anhydrous ethanol at a concentration of 15 g / L and exfoliated at 300 W for 3 h, with the circulating water temperature controlled to not exceed 35 °C. The resulting exfoliated dispersion was first centrifuged at 1800 r / min for 12 min, discarding the precipitate and collecting the supernatant. Then, it was centrifuged at 5000 r / min for 18 min, discarding the precipitate and collecting the supernatant. Finally, it was centrifuged at 9000 r / min for 25 min, discarding the supernatant and collecting the precipitate. The nanosheet thickness was verified by atomic force microscopy, and the nanosheet thickness was 100 μm. nm; The nanosheets were dispersed in anhydrous ethanol at a concentration of 7.5 g / L, and 3-aminopropyltriethoxysilane was added. The mass ratio of 3-aminopropyltriethoxysilane to nanosheets was 1:10. The mixture was stirred at 60 °C for 6 h, collected by centrifugation at 9000 r / min for 9 min, washed three times with anhydrous ethanol, and dried under vacuum at 45 °C to obtain cyclodextrin metal-organic framework nanosheets with amine-grafted surfaces.
[0083] Preparation of mono-6-ethylenediamino-β-cyclodextrin: β-cyclodextrin was dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride was added dropwise at 2°C. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride was 1:1. The pH was maintained at 10.5 with sodium hydroxide solution, and the reaction was carried out for 4 h. After recrystallization from cold water, mono-6-p-toluenesulfonyl-β-cyclodextrin was obtained. This was then mixed with ethylenediamine at a molar ratio of 1:35 and reacted at 60°C for 12 h. The mixture was precipitated with acetone and dried to obtain mono-6-ethylenediamino-β-cyclodextrin.
[0084] Preparation of cyclodextrin-resistant nanofiltration membranes. Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent of water and ethanol at a volume ratio of 4:1. The solution was heated to 50°C to dissolve, and an ethanol solution of β-ionone was added dropwise. The molar ratio of mono-6-ethylenediamino-β-cyclodextrin to β-ionone was 1:1.2. The mixture was stirred at 45°C for 4 h for inclusion, and the inclusion rate was determined to be 88% by UV spectrophotometry. The inclusion solution was concentrated under reduced pressure until the ethanol volume fraction was less than 5%. After centrifugation, the precipitated free β-ionone was discarded, and the solution was diluted with pure water to obtain a site-occupied inclusion monomer solution. Piperazine was added to the solution, with a molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine of 1:1 and a total concentration of 20 g / L. Sodium carbonate was added to adjust the pH to 10 to obtain an aqueous phase. Trimethylbenzene chloride was dissolved in n-hexane at a concentration of 2... g / L, to obtain the oil phase; immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 2 min, remove and drain; disperse cyclodextrin metal-organic framework nanosheets grafted with amine groups in a mixed solvent of n-hexane and isopropanol at a volume ratio of 10:1, with a nanosheet concentration of 0.5 g / L; immerse the support membrane in the dispersion and remove, repeat the dip-coating 3 times, without drying; within 5 min after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain a positive pressure of 0.01 MPa, and the outer surface reacts with the oil phase for 5 min; after removal, heat-treat at 70℃ for 5 min, and then contact the membrane with a hexane solution with a concentration of 0.3 g / L for 45 minutes. The membrane was dried at 40℃ and eluted with ethanol until the content of β-ionone in the eluent was below the detection limit as detected by gas chromatography. The ethanol eluent was then distilled under reduced pressure, and the distilled ethanol was reused for elution. The β-ionone at the bottom of the vessel was reused for inclusion at the site to obtain a cyclodextrin solvent-resistant nanofiltration membrane. The selective layer was located on the outer surface of the hollow fiber, and the thickness of the selective layer was measured to be 160 nm.
[0085] Example 4
[0086] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0087] Crosslinked polyimide hollow fiber support membrane was prepared. Polyimide was dissolved in N-methylpyrrolidone (20% by mass), and polyvinylpyrrolidone (1:3 by mass) was added. The mixture was stirred at 60°C to dissolve, allowed to stand to remove bubbles, and a polyimide spinning solution was obtained. Dry-jet wet spinning was performed with water as the core solution and water as the coagulation bath, with an air gap of 10 cm. The resulting hollow fibers were soaked in pure water for 36 h, then immersed in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane (8% by volume), with a 3-aminopropyltriethoxysilane to ethylenediamine mass ratio of 1:10. Crosslinking was carried out at room temperature for 18 h, followed by immersion in a 1:1 mixture of water and ethanol, and incubated at 45°C for 3 h. After removal, the membrane was washed three times with ethanol and dried at 45°C to obtain the crosslinked polyimide hollow fiber support membrane, with a molecular weight cutoff of 15000 Da.
[0088] Preparation of cyclodextrin metal-organic framework nanosheets. γ-Cyclodextrin and potassium hydroxide were dissolved in pure water at a molar ratio of 1:8, resulting in a γ-cyclodextrin concentration of 30 g / L. Anhydrous ethanol was added and mixed, with a pure water to anhydrous ethanol volume ratio of 1:1.5. Crystallization was performed at 300 W ultrasonic power, 40 kHz frequency, and 30℃ for 4 h. The mixture was then centrifuged at 9000 r / min for 8 min, and the precipitate was collected. The precipitate was washed three times with anhydrous ethanol and dried under vacuum at 45℃ to obtain cyclodextrin metal-organic framework crystals. The crystals were dispersed in anhydrous ethanol at a concentration of 15 g / L and exfoliated at 400 W ultrasonic power for 2 h, with the circulating water temperature controlled to not exceed 35℃. The resulting exfoliated dispersion was first centrifuged at 1800 r / min for 12 min, discarding the precipitate and collecting the supernatant. Then, it was centrifuged at 5000 r / min for 18 min, discarding the precipitate and collecting the supernatant. Finally, it was centrifuged at 9000 r / min for 25 min, discarding the supernatant and collecting the precipitate. The nanosheet thickness was verified by atomic force microscopy, and the nanosheet thickness was 100 μm. nm; The nanosheets were dispersed in anhydrous ethanol at a concentration of 7.5 g / L, and 3-aminopropyltriethoxysilane was added. The mass ratio of 3-aminopropyltriethoxysilane to nanosheets was 1:15. The mixture was stirred at 50 °C for 6 h, collected by centrifugation at 9000 r / min for 9 min, washed three times with anhydrous ethanol, and dried under vacuum at 45 °C to obtain cyclodextrin metal-organic framework nanosheets with amine-grafted surfaces.
[0089] Preparation of mono-6-ethylenediamino-β-cyclodextrin: β-cyclodextrin was dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride was added dropwise at 2°C. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride was 1:1.1. The pH was maintained at 10.5 with sodium hydroxide solution, and the reaction was carried out for 3 h. The mixture was then recrystallized from cold water to obtain mono-6-p-toluenesulfonyl-β-cyclodextrin. This mono-6-cyclodextrin was then mixed with ethylenediamine at a molar ratio of 1:35 and reacted at 70°C for 9 h. The mixture was precipitated with acetone and dried to obtain mono-6-ethylenediamino-β-cyclodextrin.
[0090] Preparation of cyclodextrin solvent-resistant nanofiltration membranes. Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent of water and ethanol at a volume ratio of 4:1, and heated to 55°C to dissolve. An ethanol solution of β-ionone was added dropwise, with a molar ratio of mono-6-ethylenediamino-β-cyclodextrin to β-ionone of 1:1.1. The mixture was stirred at 45°C for 8 h for inclusion, and the inclusion rate was determined to be 92% by UV spectrophotometry. The inclusion solution was concentrated under reduced pressure until the ethanol volume fraction was below 5%. After centrifugation, the precipitated free β-ionone was discarded, and the solution was diluted with pure water to obtain a site-occupied inclusion monomer solution. Piperazine was added to this solution, with a molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine of 1:0.5, and the total concentration of mono-6-ethylenediamino-β-cyclodextrin and piperazine was 20 g / L. Sodium carbonate was added to adjust the pH to 10.5 to obtain an aqueous phase. Trimethylbenzene chloride was dissolved in n-hexane at a concentration of 1.25 g / L. g / L, to obtain the oil phase; immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 2 min, remove and drain; disperse cyclodextrin metal-organic framework nanosheets grafted with amine groups in a mixed solvent of n-hexane and isopropanol at a volume ratio of 7:1, with a nanosheet concentration of 1.25 g / L; immerse the support membrane in the dispersion and remove, repeat the dip-coating 3 times, without drying; within 5 min after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain a positive pressure of 0.03 MPa, and the outer surface reacts with the oil phase for 3 min; after removal, heat-treat at 70℃ for 8 min, and then contact the membrane with a hexane solution with a concentration of 0.2 g / L for 45 minutes. The membrane was dried at 50℃ and eluted with ethanol until the content of β-ionone in the eluent was lower than the detection limit by gas chromatography. The ethanol eluent was then distilled under reduced pressure, and the distilled ethanol was reused for elution. The β-ionone at the bottom of the vessel was reused for inclusion to obtain a cyclodextrin solvent-resistant nanofiltration membrane. The selective layer was located on the outer surface of the hollow fiber, and the thickness of the selective layer was measured to be 150 nm.
[0091] Comparative Example 1
[0092] The process is basically the same as in Example 4, except that mono-6-ethylenediamino-β-cyclodextrin is not added to the aqueous phase. Instead, piperazine and pyromellitic methyl chloride are polymerized at the interface to form a selective layer. No site inclusion or ethanol elution is performed. The remaining steps and parameters are the same as in Example 4.
[0093] Comparative Example 2
[0094] The process is basically the same as in Example 4, except that no inclusion complex is performed, and mono-6-ethylenediamino-β-cyclodextrin is added directly to the aqueous phase along with piperazine. The ethanol elution in step (vii) is omitted, and the remaining steps and parameters are the same as in Example 4.
[0095] Comparative Example 3
[0096] The inclusion process was basically the same as in Example 4, except that β-ionone was replaced with an equimolar amount of 1-adamantanol in the inclusion process. The inclusion rate was 88% as determined by gas chromatography. After elution with ethanol for the same time, 1-adamantanol was still detectable in the eluent by gas chromatography. The remaining steps and parameters were the same as in Example 4.
[0097] Comparative Example 4
[0098] The process is basically the same as in Example 4, except that the pre-coating in step (5) is omitted, and the cyclodextrin metal-organic framework nanosheets are not embedded in the selected layer. The remaining steps and parameters are the same as in Example 4.
[0099] Comparative Example 5
[0100] The process is basically the same as in Example 4, except that the cyclodextrin metal-organic framework nanosheets are not grafted with amines or pre-coated. Instead, they are directly dispersed in hexane containing trimesoyl chloride during the preparation of the oil phase. The dispersion concentration of the nanosheets is 1.25 g / L, which is the same as the concentration of the pre-coated dispersion in Example 4. The remaining steps and parameters are the same as in Example 4.
[0101] Comparative Example 6
[0102] The procedure is basically the same as in Example 4, except that the molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine in the aqueous phase is 1:3. The remaining steps and parameters are the same as in Example 4.
[0103] Comparative Example 7
[0104] Take the same batch of Haematococcus pluvialis ethanol extract, and concentrate it to 1 / 8 of the original volume at 50℃ using industrial standard vacuum distillation without using a membrane.
[0105] Comparative Example 8
[0106] A commercially available cross-linked polyimide solvent-resistant nanofiltration membrane with a molecular weight cutoff of approximately 400 Da was used. It was a flat sheet membrane, and the test conditions were the same as in Example 4.
[0107] Performance Test Results and Analysis
[0108] The cyclodextrin solvent-resistant nanofiltration membranes prepared in each example and comparative example were encapsulated into hollow fiber membrane modules. Before testing, the membrane samples were soaked in anhydrous ethanol for 24 h to stabilize the membrane state. The same effective membrane area was cut from the flat sheet membrane of Comparative Example 8 and subjected to the same soaking treatment. The structure of mono-6-ethylenediamino-β-cyclodextrin was confirmed by mass spectrometry and proton nuclear magnetic resonance spectroscopy. The characteristic diffraction peaks of the cyclodextrin metal-organic framework crystals were confirmed by X-ray diffraction. The thickness of the nanosheets was verified by atomic force microscopy. The thickness of the selective layer was measured by cross-sectional scanning electron microscopy. Cross-sectional observation showed that the cyclodextrin metal-organic framework nanosheets were embedded in the selective layer without exposure or aggregation. The molecular weight cutoff of the cross-linked polyimide hollow fiber supported membrane was determined by the polyethylene glycol series cutoff curve method. The cross-linked supported membrane was detected by X-ray photoelectron spectroscopy with a Si 2p signal and Fourier transform infrared spectroscopy showed a Si-O-Si absorption peak, confirming the formation of the siloxane cross-linked structure. The inclusion rate of the occupancy inclusion was determined by ultraviolet spectrophotometry. The absorbance of the solution before and after inclusion was measured at a wavelength of 296 nm, and the inclusion rate was calculated based on the difference in the content of ionone compounds in the solution before and after inclusion.
[0109] Separation performance was tested using a simulated feed solution, which was an anhydrous ethanol solution containing 1.0 g / L astaxanthin ester, 0.3 g / L oleic acid, 0.2 g / L chlorophyll a, and 0.3 g / L trioleic acid glyceride. The transmembrane pressure difference was 1.0 MPa, the temperature was 25℃, and the system operated in a cross-flow circulation mode, with the feed solution flowing through the hollow fiber shell side and the permeate flowing through the tube side. Permeate samples were collected after 30 minutes of operation. Ethanol flux was calculated by dividing the permeate volume per unit time by the effective membrane area. Astaxanthin ester content was determined by high-performance liquid chromatography (HPLC) using a C18 column and a detection wavelength of 476 nm. The astaxanthin ester rejection rate was calculated by subtracting the ratio of permeate concentration to feed concentration from 1. Oleic acid content was determined by high-performance liquid chromatography (HPLC), chlorophyll a content by spectrophotometry at a detection wavelength of 663 nm, and trioleic acid glyceride content by HPLC with an evaporative light scattering detector. The transmittance of free fatty acids, chlorophyll a, and triglycerides was calculated based on the ratio of the permeate concentration to the feed concentration. The usable cavity volume was determined using the phenolphthalein probe method. The membrane sample was immersed in a known concentration of alkaline phenolphthalein solution for static adsorption for 12 h. The change in absorbance at 553 nm before and after adsorption was measured by ultraviolet spectrophotometry and converted into the usable cavity volume per unit mass of membrane. Phenolphthalein binds weakly to the γ-cyclodextrin cavity, producing virtually no response under the given conditions; therefore, the measured usable cavity volume represents the usable cavity volume of the β-cyclodextrin cavity.
[0110] The stability test involved continuous operation of the same component for 72 hours. The astaxanthin ester rejection rate and ethanol flux were recorded before and after the operation. The retention rate and flux decay rate were calculated. After the operation, membrane samples were taken and the potassium content was determined by inductively coupled plasma atomic emission spectrometry. The potassium dissolution rate was obtained by comparing the potassium content with the initial content.
[0111] The application effect test used *Aureobasidium pluvialis* ethanol extract, pre-filtered through a 0.45 μm filter membrane, with an astaxanthin ester concentration of 1.0 g / L. The concentration was achieved at 25℃ using a two-stage cyclic concentration process. In the first stage, the transmembrane pressure difference was 0.8 MPa, concentrating to 1 / 4 of the original volume. In the second stage, the transmembrane pressure difference was 1.2 MPa, concentrating to 1 / 8 of the original volume. The retentate was collected, and ethanol was recovered under reduced pressure to obtain astaxanthin ester oleoresin. The astaxanthin ester retention rate was calculated as the ratio of the total astaxanthin ester content before and after concentration. The mass fraction of astaxanthin ester in the oleoresin was determined by high-performance liquid chromatography (HPLC) using the external standard method. The acid value of the oleoresin was determined by potassium hydroxide titration. The proportion of all-trans astaxanthin ester was calculated by HPLC using peak area normalization. Comparative Example 7 used the same batch of *Aureobasidium pluvialis* ethanol extract, directly concentrated to the same concentration under reduced pressure before testing. Comparative Example 8 was tested under the same conditions. The specific test results are shown in Tables 1-3.
[0112] As can be seen from Tables 1 and 2, the astaxanthin ester rejection rate of Example 4 was 96.5%. In Comparative Example 1, no mono-6-ethylenediamino-β-cyclodextrin was added, and there was no β-cyclodextrin cavity in the selective layer, resulting in a rejection rate of 62.4%. This indicates that the cyclodextrin cavity is the structural basis for retaining astaxanthin ester. The available cavity amount of Comparative Example 1 was 6.3 μmol / g, which is close to 4.8 μmol / g of Comparative Example 8, which was completely free of cyclodextrin. This confirms that phenolphthalein only responds to the β-cyclodextrin cavity under the test conditions.
[0113] Although Comparative Example 1 contained cyclodextrin-encapsulated metal-organic framework nanosheets, its ethanol flux was lower than that of Comparative Example 4, which did not contain encapsulated nanosheets. This is because, in the absence of mono-6-ethylenediamino-β-cyclodextrin in the aqueous phase, the network formed by piperazine alone and trimesoyl chloride is dense, covering the delivery channels of the nanosheets and preventing them from functioning. Comparative Example 2, although containing mono-6-ethylenediamino-β-cyclodextrin, did not undergo in-situ inclusion and ethanol elution. The usable cavity volume decreased from 68.5 μmol / g in Example 4 to 24.6 μmol / g, and the rejection rate correspondingly decreased to 71.8%. This indicates that the crosslinked segments entered and blocked the cavity during interfacial polymerization, directly confirming that in-situ inclusion and ethanol elution address the cavity deactivation problem, rather than the presence or absence of cyclodextrin.
[0114] The rejection rate increased from 71.8% in Comparative Example 2 to 96.5% in Example 4, which is greater than the increase in the available cavity amount from 24.6 μmol / g to 68.5 μmol / g. This indicates that the inclusion-occupying and ethanol elution not only increased the number of open cavities, but also made the cavities left after ethanol elution more oriented, thus improving the recognition efficiency of the terminal ring structure of astaxanthin ester.
[0115] Table 1. Separation performance test results
[0116] Example 1 93.5 82.6 78.4 58.6 38.5 Example 2 93.0 81.3 77.2 57.2 36.9 Example 3 94.0 83.9 79.6 59.8 39.8 Example 4 96.5 88.2 86.3 65.4 46.2 Comparative Example 1 62.4 55.8 40.2 33.5 18.6 Comparative Example 2 71.8 68.4 52.7 41.8 22.4 Comparative Example 3 85.6 80.5 70.8 52.6 35.2 Comparative Example 4 90.1 79.8 75.5 48.9 21.5 Comparative Example 5 88.7 80.9 72.3 45.2 24.8 Comparative Example 6 79.5 72.6 61.4 50.3 33.6 Comparative Example 8 84.6 58.2 18.4 12.6 28.5
[0117] Comparative Example 3 used 1-adamantanol as a site-filling agent. Although the inclusion rate reached 88%, the binding of 1-adamantanol to the cyclodextrin cavity was too strong, resulting in incomplete elution with ethanol. The residual site-filling agent occupied the cavity, and the usable amount of the cavity was 31.2 μmol / g, with a rejection rate of 85.6%, which is between Example 4 and Comparative Example 2. This indicates that the site-filling agent needs to match the end structure of the target analyte and be eluted with ethanol. The zeinone ring of β-ionone corresponds to the cyclic structure at the end of the astaxanthin ester, and both the site-filling and elution directions are suitable. Comparative Example 8 uses a commercially available solvent-resistant nanofiltration membrane. The astaxanthin ester rejection rate of 84.6% is acceptable, but the chlorophyll a permeation rate is only 18.4% and the triglyceride permeation rate is only 12.6%. Chlorophyll a, triglycerides and astaxanthin esters have similar molecular weights, and this membrane cannot separate them by molecular weight sieving. In contrast, the chlorophyll a permeation rate of Example 4 is 86.3% and the triglyceride permeation rate is 65.4%, indicating that the retention effect of the present invention comes from the superposition of cavity recognition and molecular weight sieving.
[0118] Table 2. Cavity Usable Amount and Stability Test Results
[0119] Example 1 58.2 96.8 8.2 1.8 Example 2 56.4 96.1 8.9 2.1 Example 3 59.7 97.2 7.6 1.6 Example 4 68.5 98.5 5.3 1.2 Comparative Example 1 6.3 93.5 15.8 2.8 Comparative Example 2 24.6 94.2 13.6 2.4 Comparative Example 3 31.2 95.3 9.4 2.3 Comparative Example 4 52.3 95.6 9.1 — Comparative Example 5 48.6 81.4 22.7 18.6 Comparative Example 6 38.9 92.8 11.3 2.5 Comparative Example 8 4.8 93.2 16.4 —
[0120] From Tables 1 and 2, the effects of nanosheets and pre-coating are evident. In Comparative Example 4, without the embedded cyclodextrin metal-organic framework nanosheets, the ethanol flux decreased from 46.2 L / (m²) in Example 4. 2 The concentration of ·h decreased to 21.5 L / (m 2In Comparative Example 4, the regularly arranged cavities and large free volume of the nanosheets provide a transport channel for ethanol. The available cavity volume in Comparative Example 4 was 52.3 μmol / g, lower than the 68.5 μmol / g in Example 4, indicating that the nanosheets expanded the cross-linked network, reducing the proportion of β-cyclodextrin cavities buried by the dense network. In Comparative Example 5, the nanosheets were directly dispersed in an oil phase containing trimesoyl chloride. The amino groups on the surface of the nanosheets reacted with trimesoyl chloride in advance, causing the nanosheets to agglomerate and become unanchored. The potassium dissolution rate reached 18.6%, the flux decay rate after 72 h reached 22.7%, and the retention rate was only 81.4%. This indicates that the pre-coating was not a simple adjustment of the process position, but rather avoided the premature contact between the nanosheets and the acyl chloride, allowing the nanosheets to be integrated into the polyamide-polyester cross-linked network at the moment of interfacial polymerization, preventing loss during long-term operation. The nanosheets in Comparative Examples 1 to 3, like those in the examples, were grafted with amine groups and pre-coated to introduce a selective layer. Their lower potassium dissolution rates were within expectations. Comparative Example 5 serves as a control for the anchoring effect of the nanosheets. Regarding the aqueous phase ratio, in Comparative Example 6, the molar ratio of mono-6-ethylenediamine-β-cyclodextrin to piperazine was 1:3, with piperazine becoming the main monomer. The usable cavity volume decreased to 38.9 μmol / g, and the rejection rate decreased to 79.5%, indicating that a molar amount of cyclodextrin not lower than that of piperazine ensures a sufficient density of recognition sites. The 72-hour rejection rate retention rate of all examples was above 96.1%, the flux decay rate was no higher than 8.9%, and the potassium dissolution rate was no higher than 2.1%, indicating that the anchoring effect of the cross-linked polyimide hollow fiber support layer and the sealing of pinholes and nanosheet edges by secondary contact jointly maintained the membrane's operational stability.
[0121] As shown in Table 3, in the oleoresin obtained by directly recovering the solvent from the same batch of Haematococcus pluvialis ethanol extract, the mass fraction of astaxanthin ester was 9.6%, the acid value was 33.6 mg KOH / g, and the proportion of all-trans astaxanthin ester was 90.2%. The astaxanthin ester retention rate in Example 4 was 93.0%. The retention rates of each example were consistent with the results calculated by batch concentration material balance in Table 1, and the retention rate and the rejection rate corroborated each other.
[0122] Comparative Example 7, using vacuum distillation, achieved a retention rate of 82.3%, with the proportion of all-trans astaxanthin ester decreasing from 90.2% to 78.5%. In contrast, the all-trans proportion in all examples was above 90.9%, indicating that room-temperature membrane concentration avoided oxidative degradation and cis-trans isomerization caused by heat. The acid value of the oleoresin obtained in Comparative Example 7 was 33.1 mg KOH / g, which was basically consistent with the raw material. Vacuum distillation only removed the solvent and not the free fatty acids. The acid value of the oleoresin obtained in Example 4 decreased to 8.6 mg KOH / g, and the free fatty acids were removed with the ethanol permeate. Concentration and impurity removal were completed simultaneously, and the mass fraction of astaxanthin ester in the oleoresin increased from 9.6% to 26.8%. The retention rate of Comparative Example 8 was 72.6%, and the acid value was 27.8 mg KOH / g, both lower than those in the examples, indicating that existing solvent-resistant nanofiltration membranes cannot simultaneously achieve retention and deacidification. The above results correspond one by one with the beneficial effects. Site inclusion and ethanol elution provide cavity recognition capability, pre-coated cyclodextrin metal-organic framework nanosheets provide throughput and anchoring stability, and cross-linked polyimide hollow fiber support layer provides solvent-resistant skeleton. Together, the three enable the concentration and purification of Haematococcus pluvialis ethanol extract at room temperature.
[0123] Table 3 Application effect test results
[0124] Example 1 87.4 21.4 12.4 91.2 Example 2 86.5 20.6 13.1 90.9 Example 3 88.3 22.1 11.8 91.5 Example 4 93.0 26.8 8.6 92.8 Comparative Example 1 45.8 12.5 28.6 89.5 Comparative Example 2 55.6 14.8 24.3 89.2 Comparative Example 3 74.1 18.9 15.2 90.1 Comparative Example 4 81.4 19.7 14.8 90.3 Comparative Example 5 79.1 18.2 15.6 89.0 Comparative Example 6 65.3 16.3 19.4 89.6 Comparative Example 7 82.3 8.0 33.1 78.5 Comparative Example 8 72.6 14.2 27.8 88.9
[0125] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A cyclodextrin-resistant solvent-resistant nanofiltration membrane, characterized in that, The nanofiltration membrane comprises a cross-linked polyimide hollow fiber support layer and a selective layer attached to the outer surface of the cross-linked polyimide hollow fiber support layer; the selective layer comprises a polyamide-polyester cross-linked network and cyclodextrin metal-organic framework nanosheets embedded in the polyamide-polyester cross-linked network, wherein the polyamide-polyester cross-linked network is formed by interfacial polymerization of mono-6-ethylenediamino-β-cyclodextrin, piperazine, and trimesoyl chloride; The preparation of the cyclodextrin metal-organic framework nanosheets includes the following steps: (1) Crystallization: γ-cyclodextrin and potassium hydroxide were crystallized under ultrasound, the precipitate was collected by centrifugation, washed and dried under vacuum to obtain cyclodextrin metal-organic framework crystals; (2) Exfoliation and classification: The cyclodextrin metal-organic framework crystals are dispersed in anhydrous ethanol and exfoliated under ultrasonication to obtain an exfoliated dispersion; the exfoliated dispersion is classified by differential centrifugation, the supernatant is discarded and the precipitate is taken, the precipitate is nanosheets; (3) Grafting amine groups: The nanosheets were dispersed in anhydrous ethanol, 3-aminopropyltriethoxysilane was added, and after stirring and reacting, the nanosheets were centrifuged, washed and vacuum dried to obtain cyclodextrin metal-organic framework nanosheets with amine groups grafted on the surface.
2. The cyclodextrin solvent-resistant nanofiltration membrane according to claim 1, characterized in that, The thickness of the selective layer is 80-200 nm, the thickness of the cyclodextrin metal-organic framework nanosheet is 50-200 nm, and the thickness of the cyclodextrin metal-organic framework nanosheet is less than the thickness of the selective layer.
3. The cyclodextrin solvent-resistant nanofiltration membrane according to claim 1, characterized in that, The cross-linked polyimide hollow fiber support layer has a molecular weight cutoff of 10,000-20,000 Da. The cross-linked polyimide hollow fiber support layer is obtained by dry-jet wet spinning of polyimide spinning solution to obtain polyimide hollow fibers, followed by composite cross-linking.
4. The cyclodextrin solvent-resistant nanofiltration membrane according to claim 3, characterized in that, The polyimide spinning solution uses N-methylpyrrolidone as a solvent, and the mass fraction of polyimide is 18-22%. The polyimide spinning solution also includes polyvinylpyrrolidone, and the mass ratio of polyvinylpyrrolidone to polyimide in the polyimide spinning solution is 1:(2-5).
5. The cyclodextrin solvent-resistant nanofiltration membrane according to claim 3, characterized in that, The composite crosslinking process involves immersing polyimide hollow fibers in an isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane, crosslinking at room temperature for 12-24 h, and then immersing them in a mixture of water and ethanol at a volume ratio of 1:1, and keeping them at 40-50°C for 2-4 h.
6. The cyclodextrin solvent-resistant nanofiltration membrane according to claim 5, characterized in that, In the isopropanol solution of ethylenediamine and 3-aminopropyltriethoxysilane, the volume fraction of ethylenediamine is 5-10%, and the mass ratio of 3-aminopropyltriethoxysilane to ethylenediamine is 1:(5-20).
7. The cyclodextrin solvent-resistant nanofiltration membrane according to claim 1, characterized in that, The preparation of the cyclodextrin metal-organic framework nanosheets specifically includes the following steps: (1) Crystallization: Dissolve γ-cyclodextrin and potassium hydroxide in pure water at a molar ratio of 1:8, with a concentration of γ-cyclodextrin of 20-40 g / L. Add anhydrous ethanol and mix. The volume ratio of pure water to anhydrous ethanol is 1:(1-2). Crystallize for 2-6 h at an ultrasonic power of 200-400 W, a frequency of 40 kHz, and a temperature of 25-35℃. Centrifuge at 8000-10000 r / min for 5-10 min, collect the precipitate, wash 2-3 times with anhydrous ethanol, and vacuum dry at 40-50℃ to obtain cyclodextrin metal-organic framework crystals. (2) Exfoliation and classification: The cyclodextrin metal-organic framework crystals are dispersed in anhydrous ethanol at a concentration of 10-20 g / L and exfoliated for 1-3 h under ultrasonic power of 300-500 W, with the temperature of the circulating water controlled not to exceed 35℃, to obtain the exfoliated dispersion; the exfoliated dispersion is classified by differential centrifugation, first centrifuging at 1500-2000 r / min for 10-15 min, discarding the precipitate and taking the supernatant, then centrifuging at 4000-6000 r / min for 15-20 min, discarding the precipitate and taking the supernatant, and finally centrifuging at 8000-10000 r / min for 20-30 min, discarding the supernatant and taking the precipitate, wherein the precipitate is a nanosheet with a thickness of 50-200 nm; (3) Grafting amine groups: The nanosheets are dispersed in anhydrous ethanol at a concentration of 5-10 g / L, and 3-aminopropyltriethoxysilane is added. The mass ratio of 3-aminopropyltriethoxysilane to the nanosheets is 1:(10-20). The mixture is stirred at 40-60℃ for 4-8 h, centrifuged at 8000-10000 r / min for 8-10 min to collect the mixture, washed 2-3 times with anhydrous ethanol, and dried under vacuum at 40-50℃ to obtain cyclodextrin metal-organic framework nanosheets with amine groups grafted on the surface.
8. A method for preparing a cyclodextrin solvent-resistant nanofiltration membrane as described in any one of claims 1-7, characterized in that, The preparation method includes the following steps: (i) Inclusion: Mono-6-ethylenediamino-β-cyclodextrin was dissolved in a mixed solvent and heated to 50-60℃ to dissolve. An ethanol solution of ionone compounds was added dropwise. The molar ratio of mono-6-ethylenediamino-β-cyclodextrin to ionone compounds was 1:(1-1.2). The mixture was stirred at 40-50℃ for 4-12 h to include the compounds. The inclusion solution was concentrated under reduced pressure until the ethanol volume fraction was less than 5%. After centrifugation, the precipitated free ionone compounds were discarded. The solution was diluted with pure water to obtain the inclusion monomer solution. (ii) Preparation of aqueous phase: piperazine is added to the inclusion monomer solution, the molar ratio of mono-6-ethylenediamino-β-cyclodextrin to piperazine is 1:(0.2-1), the total concentration of mono-6-ethylenediamino-β-cyclodextrin and piperazine is 10-30 g / L, sodium carbonate is added to adjust the pH to 10-11, and the aqueous phase is obtained; (iii) Preparation of the oil phase: Dissolve pyromellitic chloride in n-hexane to obtain the oil phase; (iv) Aqueous phase immersion: Immerse the cross-linked polyimide hollow fiber support membrane in the aqueous phase for 1-3 min, then remove and drain; (v) Pre-coating: The hexane and isopropanol mixed dispersion of cyclodextrin metal-organic framework nanosheets is coated on the outer surface of the support film and left to dry. (vi) Interface polymerization: Within 5 minutes after pre-coating, nitrogen gas is introduced into the hollow fiber cavity to maintain positive pressure, and the outer surface reacts with the oil phase for 1-5 minutes. After removal, heat treatment is performed. (vii) Ethanol elution: The membrane obtained in step (vi) is eluted with ethanol to obtain a cyclodextrin solvent-resistant nanofiltration membrane.
9. The method for preparing a cyclodextrin solvent-resistant nanofiltration membrane according to claim 8, characterized in that, In step (I), the preparation method of the mono-6-ethylenediamine-β-cyclodextrin is as follows: β-cyclodextrin is dissolved in water, and an acetonitrile solution of p-toluenesulfonyl chloride is added dropwise at 0-5℃. The molar ratio of β-cyclodextrin to p-toluenesulfonyl chloride is 1:(1-1.2). The pH is maintained at 10-11 with sodium hydroxide solution, and the reaction is carried out for 2-4 h. The mixture is then recrystallized from cold water to obtain mono-6-p-toluenesulfonyl-β-cyclodextrin. Mono-6-p-toluenesulfonyl-β-cyclodextrin is then mixed with ethylenediamine at a molar ratio of 1:(20-50), and the mixture is reacted at 60-80℃ for 6-12 h. The mixture is then precipitated with acetone and dried. In step (i), the volume ratio of water to ethanol in the mixed solvent is (3-5):
1. After the inclusion in step (i) is completed, the inclusion rate is determined by ultraviolet spectrophotometry, and the inclusion rate is not less than 80%. In step (v), the concentration of cyclodextrin metal-organic framework nanosheets in the dispersion is 0.5-2 g / L, the solvent is a mixed solvent of n-hexane and isopropanol in a volume ratio of (4-10):1, and the coating is applied 2-4 times. In step (vi), the nitrogen positive pressure is 0.01-0.05 MPa, the concentration of trimesoyl chloride in the oil phase is 0.5-2 g / L, the heat treatment is 60-80℃ for 5-10 min, and after the heat treatment, the membrane is contacted with a hexane solution with a trimesoyl chloride concentration of 0.1-0.3 g / L for 30-60 s and dried at 40-60℃. In step (vii), the elution endpoint is determined by gas chromatography, where the content of ionone compounds is below the detection limit. The ethanol eluent is then distilled under reduced pressure, and the distilled ethanol is reused in step (vii). The ionone compounds at the bottom of the vessel are reused in step (i).
10. An application of a cyclodextrin solvent-resistant nanofiltration membrane as described in any one of claims 1-7, characterized in that, The cyclodextrin-resistant nanofiltration membrane is used for the concentration and purification of astaxanthin esters in the ethanol extract of Haematococcus pluvialis.